Incidence and Multidrug Resistance of Pseudomonas Aeruginosa Isolated from Clinical Samples in Diyala : Insiden dan Resistensi Multidrug Pseudomonas Aeruginosa yang Diisolasi dari Sampel Klinis di Diyala - Mohammed, Enas Ammar; Hassooni, Hanan Raheem; Fadhil, Noor Muneam; AL-Biati, Haeder A. (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Pseudomonas aeruginosa is a gram-negative bacterium that plays a key role in the pathogenesis of immunocompromised individuals. Pseudomonas aeruginosa is a common cause of hospital-acquired infections, particularly in intensive care units and burn wards. This bacterium is characterized by its extreme resistance to antibiotics, which results primarily from the expression of inducible chromosomal beta-lactamase enzymes and the production of efflux pumps, which may be constitutive or inducible. It also has the unique ability to evolve resistance to virtually all available antimicrobials through mutation, in addition to its natural resistance. Objective: The study aimed to identify the most appropriate antibiotics for treating Pseudomonas aeruginosa isolated from hospitals. Materials and Methods: 160 clinical samples of burn and wound infections, urinary tract infections, otitis media infections, sputum, blood, and vaginitis and throat infections were collected from patients admitted to Baqubah Teaching Hospital, Al-Batool Teaching Hospital, outpatient clinics, women’s clinics, and the consulting clinic in the governorate. Diyala, during the period from 3\11/2022 to 15\4/2023. Results: Screening using conventional methods and biochemical tests revealed that (26) isolates (16.25%) were P. aeruginosa. All isolates recorded positive results for both the catalase and oxidase tests, while the results of the IMViC tests in all isolates showed negative results for the methyl red, indole, and Voges-Proskauer tests, and positive results for the citrate consumption test. Susceptibility testing was performed using eight types of antibiotics, and the resistance and sensitivity of the isolates were verified using the standard disk diffusion method (Kirby Power). The resistance rate was 80.76% for ticarcillin, 53.84% for cefepime, 38.46% for ciprofloxacin, 46.15% for piperacillin, 25.92% for amikacin, 30.76% for tobramycin, and 30.23% for imipenem. Conclusion: The resistance of Pseudomonas aeruginosa to antibiotics has increased over time, leading to the emergence of new strains that are classified according to their degree of resistance into: multidrug-resistant strains and extensively resistant strains.Highlight : Pseudomonas aeruginosa is a major cause of hospital-acquired infections with high resistance to antibiotics. The study revealed a high incidence of multidrug-resistant (MDR) strains, especially in wound and ear infections. Ticarcillin and Cefepime showed the highest resistance, while Amikacin was the most effective antibiotic. Keywords : Pseudomonas aeruginosa, Antibiotic Resistance, Multidrug Resistance, Clinical Samples, Diyala